Autophagy in exposure to environmental chemicals. (1st May 2019) - Pesonen, Maija; Vähäkangas, Kirsi
Highlights: Autophagy is a catabolic process that degrades and recycles cellular organelles and proteins. The level of autophagy is increased under stress conditions including chemical stress. Many environmental chemicals have been found to affect autophagy. Increase of autophagy can increase adaptation into stress and decrease genetic damage. Inhibition or depletion of autophagy process can either increase or decrease toxicity depending on the context. Abstract: Autophagy is a catabolic pathway, which breaks down old and damaged cytoplasmic material into basic biomolecules through lysosome-mediated digestion thereby recycling cellular material. In this way, autophagy prevents the accumulation of damaged cellular components inside cells and reduces metabolic stress and toxicity. The basal level of autophagy is generally low but essential for maintaining the turnover of proteins and other molecules. The level is, however, increased in response to various stress conditions including chemical stress. This elevation in autophagy is intended to restore energy balance and improve cell survival in stress conditions. However, aberrant and/or deficient autophagy may also be involved in the aggravation of chemical-caused insults. Thus, the overall role of autophagy in chemical-induced toxicity is complex and only a limited number of environmental chemicals have been studied from this point of view. Autophagy is associated with many of the chemical-caused cytotoxic mechanisms, including mitochondrial dysfunction, DNA damage, oxidative stress, changes in the endoplasmic reticulum, impairment of lysosomal functions, and inflammation. This mini-review describes autophagy and its involvement in the responses to some common environmental exposures including airborne particulate matter, nanoparticles and tobacco smoke as well as to some common single environmental chemicals.